Chomp - Hiaasen, Carl (a Yearling book, 2020)
Nick and Marta don't believe the principal when she tells them their biology teacher, Mrs. Starch, was called away on a family emergency. They think her disappearance has something to do with their field trip to Black Vine Swamp, and the class delinquent, Smoke.